Integrating Weighted Delay Index (WDI) with Dynamic Critical Path Analysis for Enhanced Delay Assessment in Construction Projects (Journal of Civil Engineering Researchers, 2026)
Project delay remains one of the most persistent challenges in construction management, often leading to significant cost overruns, contractual disputes, and stakeholder dissatisfaction. Traditional scheduling and delay analysis methods—such as Critical Path Method (CPM), Earned Value Management (EVM), and conventional Extension of Time (EOT) techniques—tend to overlook the relative importance of activities and the dynamic nature of project execution. This study introduces the Weighted Delay Index (WDI), a novel metric that integrates activity-specific weights with dynamic critical path analysis to provide a more nuanced evaluation of delay severity. Activity weights are derived through the Analytical Hierarchy Process (AHP), incorporating four key dimensions: time, cost, risk, and technical impact. The methodology is validated through multiple case studies of construction projects, where WDI trends are compared against actual project delays determined via Time Impact Analysis. Results indicate that Project Duration is the dominant predictor of overall delays, while WDI offers significant diagnostic and managerial value by identifying critical activities whose delays disproportionately affect project performance. Workforce Intensity is found to moderate delay outcomes, with higher intensity generally reducing delay severity. The proposed framework provides project managers with an early-warning and prioritization tool, enabling targeted intervention strategies that go beyond aggregated delay measures. The study contributes to both theory and practice by bridging the gap between deterministic scheduling and dynamic, activity-sensitive delay analysis.
Keywords: Construction project delays; Weighted Delay Index (WDI); Dynamic Critical Path Method; Extension of Time (EOT) methods; Delays